Can an oligotrophic coastal lagoon support high biological productivity? Sources and pathways of primary production. (January 2020) - Pérez-Ruzafa, Angel; Morkune, Rasa; Marcos, Concepción; Pérez-Ruzafa, Isabel M; Razinkovas-Baziukas, Arturas
Abstract: Coastal lagoons are among the most productive systems in the world. Many marine species make use of this by entering the lagoons as juveniles for nursery and growth before returning to the sea for reproduction. Humans take advantage of such fish migration processes by fishing, and exploit the high productivity for aquaculture activities. The Mar Menor is one of the largest coastal lagoons in the Mediterranean, sustaining relatively high fishing intensity despite the fact that it has traditionally been characterized as highly oligotrophic. However, in the last decades, this lagoon has suffered drastic changes induced by human activities. This has led to eutrophication, which started mainly as a consequence of changes in agricultural practices in the lagoon watershed, and triggered such fundamental changes in the system, as the mass development of jellyfish. The aim of this work is to capture and analyse the structure and functioning of the trophic web of the Mar Menor when it was still, in contrast to other coastal lagoons, oligotrophic, to provide a start point for analysing the consequences of changes in the distribution of macrophyte meadows and of eutrophication. We have compiled a detailed trophic model of this lagoon, comprising 94 compartments, using an ECOPATH model to capture the period 1980–1995. At this time the lagoon was an autotrophic system with a high net surplus of production that reached 9124.31gC/m 2 /year, while the production/biomass (P/B) ratio reached 34.56 and the total primary production/total respiration ratio was 7.01. The lagoon exported a 38.46% of total flows, including the catch by fishing, and 44.40% went to detritus. The primary production was mainly benthic (99.4%) due to the microphytobenthos and macrophytes. However, despite the fact that total fishery landings in the study period ranged between 144, 835.5 and 346, 708.5 kg, the gross efficiency was low, making up only 0.005% of the net primary production. This could partly be explained by the high trophic level of the fish catch (2.9), but mainly because most of the primary production (10, 532.06 gC/m 2 /year) went directly to the detritus pool and was accumulated in the sediment in the Caulerpa prolifera meadows. We suggest several reasons why such high productivity coincided with low chlorophyll concentrations and good overall water quality: 1) the domination of both benthic biomass and primary production over pelagic ones with a high biomass of filter feeders, detritus feeders and scavengers, 2) high species diversity, complex and long food webs characterized by low connectance, 3) the export of a significant part of the production from the system, and 4) the accumulation of surplus organic matter (as detritus) in sediments. We compare the food web of the Mar Menor in this mentioned oligotrophic stage to those of ten other lagoons in pursuit of more general implications regarding lagoon ecosystem functioning. Graphical abstract: Image 1 Highlights: Coastal lagoons can share both characteristics of highly productive systems and also of well-structured and complex ones. Regulatory mechanisms preclude the acceleration of the system, maintaining low chlorophyll and good quality water column. Priorizing benthic over pelagic production, with high biomass of filter and detritus feeders and scavengers. Exporting part of the production out of the system. Accumulating the excess of production in the sediments.